Effects of gamma irradiation on the electrical characteristics of trench-gate non-punch-through insulated gate bipolar transistor. (22nd May 2019) - Baek, Hani; Yoon, Tae-Sik; Sun, Gwang Min; Shin, Chansun
Abstract: We studied the effects of gamma-ray irradiation on the static and dynamic electrical characteristics of a trench-gate non-punch-through insulated gate bipolar transistor (IGBT) device. The threshold voltage and breakdown voltage decreased after irradiation, whereas the collector leakage current increased. Turn-on and turn-off switching times decreased and increased, respectively, with the irradiation dose. The irradiation-induced changes in the electrical characteristics can be attributed to the buildup of the positive oxide-trapped charges in the gate oxide by gamma irradiation. The evaluated characteristics data were compared with the data for gamma-irradiated planar-gate IGBTs reported in the literature. It was found that a significant degradation occurred in the shift of the threshold voltage and switching times for trench-gate IGBTs.